The net, our means to increase communication in the world of high performance sport. (2nd International Forum on Elite Sport. Barcelona, Centre d'Alt Rendiment (C.A.R.) de Catalunya, 11-13 September 2001, 2001)
The net, our means to increase communication in the world o of high performance spor sport. Chairman: Josep Escoda - Head of Sports Sciences R&D, Centre d`Alt Rendiment, Sant Cugat, Spain Panellists: Ramon Garcia, Universitat Autònoma de Barcelona, Spain Josep M. Fortuny i Aymemi, Universitat Autònoma de Barcelona, Spain Joaquín Jiménez, Universitat Oberta de Catalunya, Spain Xavier Balius Matas, C.A.R. (Centre d'Alt Rendiment), Sant Cugat, Spain Andreu Roig, C.A.R. (Centre d'Alt Rendiment), Sant Cugat, Spain